1996
DOI: 10.1159/000109176
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Signaling in Goldfish Pituitary Cells

Abstract: In goldfish, maturational gonadotropin (GTH) and growth hormone (GH) release are stimulated by two native GTH-releasing hormones (sGnRH and cGnRH-II). Both GnRHs stimulate GTH and GH release via activation of phospholipase C, protein kinase C, Ca2+ entry through voltage-sensitive channels and calmodulin. However, sGnRH-induced GTH release also involves arachidonic acid and intracellular Ca2+ components absent from its action on GH, as well as from cGnRH-II action on GTH and GH secretion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Results from studies on the brain distribution of GnRH protein and mRNA also support the view that both peptides act as hypophysiotropic neurohormones in goldfish (reviewed in Yu et al 1998). The presence of GnRH receptors on both GTH-II and GH cells, the ability of sGnRH and cGnRH-II to stimulate GTH-II and GH release from pituitary cell preparations, as well as correlative changes in brain GnRH content during physiological modulations of serum GTH-II and GH levels, are consistent with a role of both sGnRH and cGnRH-II as neuroendocrine regulators of gonadotrope and somatotrope functions (reviewed in Chang et al 1996b;Peng and Peter 1997). It has been suggested that GTH-II and GH cells possess different GnRH receptors, or suites of receptors (reviewed in Chang et al 1996b;Illing et al 1999).…”
Section: Gnrh Peptides and Receptorsmentioning
confidence: 74%
See 4 more Smart Citations
“…Results from studies on the brain distribution of GnRH protein and mRNA also support the view that both peptides act as hypophysiotropic neurohormones in goldfish (reviewed in Yu et al 1998). The presence of GnRH receptors on both GTH-II and GH cells, the ability of sGnRH and cGnRH-II to stimulate GTH-II and GH release from pituitary cell preparations, as well as correlative changes in brain GnRH content during physiological modulations of serum GTH-II and GH levels, are consistent with a role of both sGnRH and cGnRH-II as neuroendocrine regulators of gonadotrope and somatotrope functions (reviewed in Chang et al 1996b;Peng and Peter 1997). It has been suggested that GTH-II and GH cells possess different GnRH receptors, or suites of receptors (reviewed in Chang et al 1996b;Illing et al 1999).…”
Section: Gnrh Peptides and Receptorsmentioning
confidence: 74%
“…The presence of GnRH receptors on both GTH-II and GH cells, the ability of sGnRH and cGnRH-II to stimulate GTH-II and GH release from pituitary cell preparations, as well as correlative changes in brain GnRH content during physiological modulations of serum GTH-II and GH levels, are consistent with a role of both sGnRH and cGnRH-II as neuroendocrine regulators of gonadotrope and somatotrope functions (reviewed in Chang et al 1996b;Peng and Peter 1997). It has been suggested that GTH-II and GH cells possess different GnRH receptors, or suites of receptors (reviewed in Chang et al 1996b;Illing et al 1999). Recently, cDNAs encoding two goldfish GnRH receptors have been cloned, and their presence in the pituitary confirmed (Yu et al 1998;Illing et al 1999).…”
Section: Gnrh Peptides and Receptorsmentioning
confidence: 83%
See 3 more Smart Citations